2015
DOI: 10.1002/2327-6924.12127
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and stress in adult Hispanics

Abstract: Purpose Physical inactivity and obesity are major U.S. health concerns. Hispanics have higher rates of obesity and lower incidence of meeting physical activity (PA) recommendations, however most studies on PA focus on non‐Hispanic Whites. This study examined type and amount of physical activities, and their relationship to age, BMI, employment, and stress in adult female Hispanics. Data sources Sixty‐three female Hispanics (mean age 34 years, SD = 10.5) were recruited in the Miami community. By BMI, of 47 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[ 21 ] and Chai et al [ 28 ] also noted positive correlations between physical activity and the psychological domain of quality of life. There have been confirmed relationships between physical activity and such factors as optimism and joy of life [ 49 ], visual attention [ 50 ], self-esteem [ 51 ], and reduced anxiety or depression [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] and Chai et al [ 28 ] also noted positive correlations between physical activity and the psychological domain of quality of life. There have been confirmed relationships between physical activity and such factors as optimism and joy of life [ 49 ], visual attention [ 50 ], self-esteem [ 51 ], and reduced anxiety or depression [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that show correlations between physical exercise and stress. Hannan et al proved that physical inactivity was correlated with a high level of stress [ 30 ] while Vankim et al showed in their study on college students that high-intensity exercise was less likely to be correlated with poor mental health and perceived stress [ 31 ]. Another study reported that exercise had a positive effect on physical and emotional quality of life [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] and Chai et al [14] found positive correlations between PA and the psychological domain of Qol. There have been confirmed relationships between PA and factors such as optimism and joy of life [34], visual attention [35], self-esteem [36], and reduced anxiety or depression [37]. Additionally, Thiel et al [38] found a significant positive association between PAL and HRQL, particularly physical health.…”
Section: Discussionmentioning
confidence: 90%